Analyze The Effects of Helical Baffles Angles Variation On Shell Side Heat Transfer Coefficient And Pressure Drop of Shell And Tube Heat Exchange - Linta Atina Rahmah; Devy Setiorini Sa’adiyah; Sulistijono Sulistijono (SPECTA Journal of Technology, 2018)
E-201-11 is one of the components of heat exchanger which serves to increase the temperature of distillated crude oil before it going into the furnace. The use of segmental baffles on the heat exchanger causes dead zone. The fouling phenomenon that arises from the deposition of the compound content in the service fluid in dead zone can result in leakage of the shell and tube. It affects the performance of heat exchanger and production efficiency. The use of discontinuous helical baffle on the shell side minimizes fouling. Research on the variation of helical baffle angle by using Bell-Delaware method resulted in performance value of heat transfer coefficient and pressure drop on the shell side. Fluid flow behavior on the shell side with helical baffle was analyzed by Computational Fluid Dynamics (CFD). The fluid flow velocity is a factor that affects the value of heat transfer coefficient and pressure drop. Heat exchanger with an angle of 10º have fluid flow velocity of 0,893m/s resulting in the highest heat transfer coefficient and pressure drop value compared to angles of 15º and 20º with values of 585.725W/m²K and 13642.395Pa. The heat exchanger with helical baffle at 10° helix angle presents the best performance among the others variant helical baffles